1. Rewrite one of the equations in terms of one variable (in this case, x = 2y + 11).
2. Substitute the expression for that variable into the other equation.
3. Solve the resulting equation for the remaining variable (in this case, y).
4. Substitute the value of y back into the equation x = 2y + 11 to find the value of x.
5. Check the solution by substituting the values of x and y into both original equations to see if they are true.
6. Write the final solution as an ordered pair (x, y).
Put the steps in order that are used to solve the following systems of equations by substitution. −7x−2y=−13 x−2y=11 (10 points)
y = -4
x = 3
(3,-4)
x -2y = 11 --> x = 2y + 11
x - 2(-4) = 11
x + 8 = 11
-14y - 77 - 2y = -13
-16y = 64
-16y - 77 =-13
-7(2y + 11) - 2y = -13
1 answer